Fluorometric "Turn-On" glucose sensing through the in situ generation of silver nanoclusters. Issue 3 (5th January 2017) - Chen, Yang; Sun, Yuanqing; Song, Rongjun; Song, Shanliang; Zhao, Yue; Yang, Xudong; Yu, Cong; Lin, Quan
Abstract : A fluorometric "turn-on" glucose detection is performed based on the Fenton reaction which can trigger the generation of Ag nanoclusters. Abstract : Fluorometric "turn-on" glucose detection is presented that is based on the Fenton reaction which can trigger the generation of Ag nanoclusters (Ag NCs). Oxidation ofd -glucose by glucose oxidase generates H2 O2 . Reactive radicals are formed from the Fenton reaction of H2 O2 and Fe 2+ . These radicals initiate the polymerization of methacrylic acid to form poly(methacrylic acid) which is used as a template to generate fluorescent Ag NCs in situ by illumination with UV light. The increase in Ag NCs fluorescence intensity can be used to quantify glucose concentration. The sensing approach employed here provides a new strategy for the determination of glucose selectively.